Effect of feeding rendered poultry slaughter byproduct meal on growth and immunocompetance of growing turkey poults - AWACHAT, V B; MAJUMDAR, S; MANDAL, A B; BHANJA, S K (The Indian Journal of Animal Sciences, 2012)
The present study was conducted to assess the feeding value of poultry slaughter byproduct meal (PSBM) and its effect on immune response in growing turkey poults. Day-old turkey poults (150) were distributed into 5 dietary treatments, T 1 (0%), T 2 (2.5%), T 3 (5%), T 4 (7.5%) and T (10% PSBM), having 3 replicates of 10 birds/replicate. Each dietary treatment was fed ad lib. in 2 phases i.e. starter (0–4 wk, 28% CP and 2800 Kcal ME/kg) and developer (4–8 wk, 26% CP and 2900 Kcal ME/kg). The poults fed 7.5% or 10% PSBM had significant less body weight, feed intake and poorer feed conversion compared to those on 0% PSBM (T 5 1 ) diet at 8 wk of age, but these parameters did not differ among the diets containing 0% to 5% PSBM. There was no significant difference in the relative weight of immune organs and immune response among different treatment groups. These observations suggested that inclusion of poultry slaughter byproduct meal up to 5% in diet replacing soybean meal had no adverse effect on body weight, feed intake and feed utilization efficiency but at higher levels (7.5 or 10%) of inclusion of PSBM as a source of protein decreased the body weight gain of growing turkey poults. Therefore, poultry slaughter byproduct meal can safely and effectively be incorporated up to 5% level without adverse effect on immuno-competence.